POLA KEPEMIMPINAN KH. ARIFIN ILHAM DALAM PENGEMBANGAN YAYASAN AZ-ZIKRA SENTUL KABUPATEN BOGOR - Mubarraq, Alwahyu (Institut Agama Islam Sahid Bogor, 2024)
Leadership in the Az-Zikra Islamic boarding school is an effort to educate students who are led in this case by a pesantren leader to teachers, students and staff to carry out pesantren activities that have been discussed with the aim of carrying out effectively as taught by the great prophet Muhammad SAW. The problem that researchers encountered was that the previous leadership at the Azzikra Islamic Boarding School was due to a leadership figure, KH. Muhammad Arifin Ilham so that after his death no one could be like the figure of murabbi KH. Muhammad Arifin Ilham therefore the importance of a leadership system in the Az-Zikra Islamic boarding school so that whoever leads it continues as usual because the pesantren system that has been planned is in accordance with the ideals of KH. Muhammad Arifin Ilham.